PENINGKATAN PROFESIONALISME GURU DAN PENGEMBANGAN SDM DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 PADA GURU SMK MULIA BUANA PARUNG PANJANG BOGOR - Effendy, Aidil Amin; Sudarso, Aden Prawiro; Nurhadi, Ahmad; Arifianto, Chandra Fitra; Kartono, Kartono (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service aims to help open the paradigm of Mulia Buana Parung Panjang SMK teachers to want to explore in teaching and provide an understanding of the real conditions outside of the threat of the Industrial Revolution 4.0. which was then given material on developing the skills of SMK Mulia Buana's teachers in implementing creative and innovative teaching in accordance with the development of the Industrial Revolution 4.0. The problem faced by the Mulia Buana Parung Panjang Vocational School Teacher is the lack of ability of the Mulia Buana Parung Panjang Vocational School teacher in mastering technology and many teachers who have not been able to utilize ICT devices for teaching and learning. This certainly has an impact on the lack of enthusiasm for student learning. Through the training method in the form of providing material and practice, at the end of the activity a question and answer session was conducted as a form of evaluation, the teachers received training in soft skills and hard skills. The results after attending the training given by Pamulang University lecturers, the ability of Mulia Buana Parung Panjang Vocational School teachers to increase. It's just that it needs to be maintained regularly and improved the ICT support devices.